Vaginal Recanalization after 15 Years Closed due to Post Partum Infection - Melly Liman; Melani Limenco Benly (Science Midwifery, 2023)
Synechiae labia, is also called adhesi labia or agglutination of the labia, is a disorder occurred to the women genitalia with the characteristic of thin labia, the presence of a membrane attached to the labia minora. The incidence rate of synechiae labia in adolescent women is 1 to 5% , while in infant girls is about 10% in the first year of life. However, it is very rare in women with reproductive age. This research is conducted to the patient of 43 years old with synechiae labia. On physical examination, labia minora were found attached to each other towards the clitoris in patients performed operative introitoplasty and administration of antibiotics